Shakespeare's ghosts live : from Shakespeare's ghosts to psychical research - Puhle, Annekatrin, 1953-; Adrian Parker-Reed (Cambridge Scholars Publishing, 2017)
Shakespeare has been one of the most-cited authors since his plays were performed, and yet little attention has been paid to his views on psychic phenomena. It took another 300 years of paranormal experiences before scholars at Cambridge University helped to found the Society for Psychical Research, which brought scientific scrutiny to the area, and the UK is now a world leader in university research on this topic. This book throws new light on many historical case reports from Shakespeare's time onwards. It identifies the core experiences that transcend time and give clues to an understanding.